Ecological Status Assessment of Transitional Waters - FACCA, Chiara (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Coastal transitional ecosystems include a wide range of morphological features-i.e., lagoons, wetlands, estuaries, deltas, and so on. According to the Ramsar Convention, "they are among the most diverse and productive ecosystems" and are continually "degraded and converted to other uses". To protect and restore these highly valuable ecosystems, knowledge of their processes and the assessment of their ecological conditions under anthropogenic pressures is of fundamental importance. The present book contains eight original research papers and a review that provide useful tools to understand the structure and function of transitional waters worldwide. The results allow us to assess the impact of anthropogenic activities and inform stakeholders on the actions that can be taken to manage them. The papers in this book provide different ecological approaches to investigate some main impacts: - benthic and nekton communities were studied to assess the impact of eutrophication and salinity changes; - biological processes in carbon dioxide fluxes were assessed in the framework of climate change; - nekton communities were discussed in relation to habitat morphological degradation; - the role of invasive alien species was considered.